The Crypt: Probing the Obscure Administration of Cultural Memory - Redin, Johan (Temenos, 2011)
The prescribed means to engage with the past through a variety of culturally upheld techniques is receiving wider attention within the humanities today. This is partly due to the growing field of so-called ‘cultural memory studies’. Religion is typically evoked in these circumstances as an exemplary entry into processes of long-term cultural mediation, and the different interests permeating the maintenance and obfuscation of a time-honoured past. The article is devoted to a concept that has attracted comparatively little attention among students of cultural memory: the crypt and its various analogies to the question of remembrance without memory.